Accounting and the ERP systems: case study - Machado, M. (2018)
This case study has the following specific objectives: to identify the reasons for implementing SAP ERP; to identify the main benefits and problems resulting from its adoption; to understand in what way accounting is integrated in SAP ERP; to analyse how SAP ERP influences the accountants’ role. The chosen method of investigation was the descriptive case study, with recourse to various sources of data collection. These were: semi-structured interviews as the main method of data collection; direct observation; document collection. This study’s main contributions are the following: the resistance to change phenomenon, suggested by theory as a major problem in ERPs implementation, was not found; SAP ERP does not allow all of the accounting objectives to be achieved, making the use additional software a necessity due to its lack of flexibility and the need for specialized technicians when any changes have to be made.